A robust definition of energy effectiveness for humidification dehumidification desalination systems. (15th June 2021) - AlSaif, Abdulaziz A.; Elzayed, Mohamed S.; Ahmed, M.A.M.; Antar, M.A.; Zubair, Syed M.
Highlights: An innovative energy effectiveness model is proposed to examine an HDH system. The proposed method eliminated the possibility of a humidifier temperature cross. The probability of second law violation is eliminated in the proposed method. The optimization of the system's controllable parameters is explained. Direct design procedure is suggested to size HDH system components. Abstract: Humidification-dehumidification (HDH) is a cost-effective thermal desalination system that utilizes low-grade energy to extract freshwater from high salinity seawater with minimum maintenance. A robust method is presented using an innovative definition for energy effectiveness to facilitate the practical utilization of HDH modeling in the design process. This definition is mainly based on representing the flow stream on the temperature-enthalpy diagram to locate the pinch point and overcome the terminal-based definition limitation accordingly. The possible violation of the Second Law of Thermodynamics is the main drawback of the previous definitions due to the temperature-cross inside the humidifier, which defeats the purpose of air heating and humidification. The closed-air open-water HDH model is examined thermodynamically, and its design characteristics are explored at different operating conditions. The proposed definition is compared with analogous data from the literature. It showed an excellent agreement with a maximum discrepancy of 2.30%. Furthermore, a direct and straightforward design scheme is provided to estimate the dehumidifier and humidifier sizes based on the location and amount of freshwater needed. A case study for a system that produces 5 kg h −1 of freshwater in Dhahran is presented. The optimal energy effectiveness is found to be 78%, where the average minimum and maximum temperature of seawater in the system are assumed to be 25 and 70 °C, respectively.